Frontiers in pruritus research: scratching the brain for more effective itch therapy - Ralf Paus; Martin Schmelz; Tamás Bíró; Martin Steinhoff (The Journal of Clinical Investigation, 2006)
This Review highlights selected frontiers in pruritus research and focuses on recently attained insights into the neurophysiological, neuroimmunological, and neuroendocrine mechanisms underlying skin-derived itch (pruritogenic pruritus), which may affect future antipruritic strategies. Special attention is paid to newly identified itch-specific neuronal pathways in the spinothalamic tract that are distinct from pain pathways and to CNS regions that process peripheral pruritogenic stimuli. In addition, the relation between itch and pain is discussed, with emphasis on how the intimate contacts between these closely related yet distinct sensory phenomena may be exploited therapeutically. Furthermore, newly identified or unduly neglected intracutaneous itch mediators (e.g., endovanilloids, proteases, cannabinoids, opioids, neurotrophins, and cytokines) and relevant receptors (e.g., vanilloid receptor channels and proteinase-activated, cannabinoid, opioid, cytokine, and new histamine receptors) are discussed. In summarizing promising new avenues for managing itch more effectively, we advocate therapeutic approaches that strive for the combination of peripherally active antiinflammatory agents with drugs that counteract chronic central itch sensitization.